2020
DOI: 10.2217/fon-2020-1055
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological, Molecular Features and Prognosis of Colorectal Cancer with Mucinous Component

Abstract: Background: Colorectal cancer (CRC) with mucinous component is associated with distinct characteristics and controversial prognosis. Patients & methods: A total of 1800 CRC patients were retrospectively enrolled and grouped by the mucinous content of the primary tumors. The clinicopathological characteristics and overall survival rate were compared between groups. Results: Mucinous adenocarcinoma (MAC) and adenocarcinoma with mucinous component (AMC) had higher frequencies of DNA mismatch repair protein de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
3
6
1
Order By: Relevance
“…S2B). Mucinous dedifferentiation was associated with the CIMP-H/MSI phenotype, a high frequency of BRAF and KRAS mutations, and fewer changes in the p53 pathway, consistent with the literature [29] (Additional file 1: Fig. S2C, D, S3A).…”
Section: Downregulation Of Ly6g6d Characterizes Mucinous Colon Adenoc...supporting
confidence: 88%
See 2 more Smart Citations
“…S2B). Mucinous dedifferentiation was associated with the CIMP-H/MSI phenotype, a high frequency of BRAF and KRAS mutations, and fewer changes in the p53 pathway, consistent with the literature [29] (Additional file 1: Fig. S2C, D, S3A).…”
Section: Downregulation Of Ly6g6d Characterizes Mucinous Colon Adenoc...supporting
confidence: 88%
“…All cases were also analyzed for mismatch repair protein expression by IHC. More than 50% of mucinous tumors were MMR-deficient, compared to 15% of classical adenocarcinomas, which is consistent with the literature [29]. Next, we examined the tumor microenvironment for infiltration of LY6G6D + cells in mucinous and non-mucinous tumors.…”
Section: Proteogenomic Profiling Reveals Dna Methylation Changes In M...supporting
confidence: 86%
See 1 more Smart Citation
“…Indeed, the effect of MAC on the survival of colon MAC patients remains debatable. Several studies have demonstrated that the MAC subtype was associated with a worse prognosis 6,9–11,24–26 . In a population‐based survival study, MAC had a poor outcome because of advanced disease 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the MAC subtype was associated with a worse prognosis. 6,[9][10][11][24][25][26] In a population-based survival study, MAC had a poor outcome because of advanced disease. 27 This association has been confirmed in a large metaanalysis.…”
Section: Refmentioning
confidence: 99%